2005
DOI: 10.1007/s11664-005-0207-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rare earth element addition on the microstructure of Sn-Ag-Cu solder joint

Abstract: The effects of minimal rare earth (RE) element additions on the microstructure of Sn-Ag-Cu solder joint, especially the intermetallic compounds (IMCs), were investigated. The range of RE content in Sn-Ag-Cu alloys varied from 0 wt.% to 0.25 wt.%. Experimental results showed that IMCs could be dramatically repressed with the appropriate addition of RE, resulting in a fine microstructure. However, there existed an effective range for the RE addition. The best RE content was found to be 0.1 wt.% in the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 5 publications
0
49
0
Order By: Relevance
“…As also indicated by the Cu-Sn phase diagram, the intermetallic Cu6Sn5 phase with approximately 53.5 at % Cu and 46.5 at % Sn and having the typical hollow hexagonal shape was formed in all alloys, together with the β-Sn [20]. The hollow-stick-type Cu6Sn5 forms when the core of the rod dissolves due to the higher energy of screw dislocation and lower Cu concentration, and fills with molten solder [21] during reflow soldering; after solidification, the Cu atoms will diffuse into solidified solder from the Cu substrate, and based on screw dislocation mechanism, a long hollow will appear in the Cu6Sn5 whisker. Moreover, Zhang [22] proposed that the screw dislocation core can be produced by the mismatch of atoms during the formation of Cu6Sn5, which will result in rapid lateral growth to form the special structure of the Cu6Sn5 whisker.…”
Section: Methodsmentioning
confidence: 77%
“…As also indicated by the Cu-Sn phase diagram, the intermetallic Cu6Sn5 phase with approximately 53.5 at % Cu and 46.5 at % Sn and having the typical hollow hexagonal shape was formed in all alloys, together with the β-Sn [20]. The hollow-stick-type Cu6Sn5 forms when the core of the rod dissolves due to the higher energy of screw dislocation and lower Cu concentration, and fills with molten solder [21] during reflow soldering; after solidification, the Cu atoms will diffuse into solidified solder from the Cu substrate, and based on screw dislocation mechanism, a long hollow will appear in the Cu6Sn5 whisker. Moreover, Zhang [22] proposed that the screw dislocation core can be produced by the mismatch of atoms during the formation of Cu6Sn5, which will result in rapid lateral growth to form the special structure of the Cu6Sn5 whisker.…”
Section: Methodsmentioning
confidence: 77%
“…The reason may be that the second phase reinforcing Ni nano-particles promote a high nucleation density in the eutectic colonies during solidification. Li et al [28] reported that rare earth elements reduce the rate of IMC layer growth in two ways i.e. by altering the diffusion coefficient and the thermodynamic parameters of elemental affinity.…”
Section: Resultsmentioning
confidence: 99%
“…The plausible explanation for appearing fine microstructure for Sn-Bi-Ag solder joints on Au/Ni-plated Cu substrate was that the thin Au layer dissolved into the solder matrix during reaction and formed very fine Au 4 Sn IMC which inhibited the formation of grain growth. In the earlier literature, Li et al [40] added trace amount of rare earth element into lead-free Sn-based solder alloys and found that the adding trace amount of rare earth elements significantly reduced the IMC formation in two ways i.e., by changing the diffusion coefficient and thermodynamic parameters of the elemental affinity. Ni-plated Cu substrate, were found to be adhered at their interfaces.…”
Section: Microstructure Of Sn-bi-ag Based Soldersmentioning
confidence: 99%